The Role of Insights in Becoming a Culturally Responsive Mathematics Teacher - Kathleen T. Nolan; Constantinos Xenofontos (MDPI AG, 2023)
This paper extends earlier research on prospective and practicing teachers' (PPTs') developing understandings of culturally responsive pedagogy (CRP) while enrolled in a teacher education course for CRP and mathematics. Here, we take as our starting point a framework we refer to as COFRI, which describes five integral components of PPTs' perspectives on CRP: Challenges, Opportunities, Fears, Resistance, and Insights. Viewing PPTs' reflective journal entries through the lens of this framework, we noticed interesting relationships between the five components that had not been evident in our initial analysis. Specifically, we observed that, as we coded participants' reflections according to C, O, F, R, and I, each I (insight) appeared to be related to one (or more) of the other components in quite different ways. Additionally, careful study of the insights expressed by PPTs lead to our categorization of insights according to one of three types: mathematical, pedagogical, or ideological. As a result, this paper offers a new way to interpret the five components, specifically their relationships to new insights into CRP and the corresponding types of insights that PPTs produce over the course of one semester. In closing, this paper discusses implications for mathematics teacher educators in understanding and processing PPTs' evolving understandings of CRP.